Intimal sarcoma of the pulmonary artery treated with neoadjuvant radiation prior to pulmonary artery resection and reconstruction. (2021) - Allen, Alexander; Smith, Steven C.; Pillappa, Raghavendra; Boikos, Sosipatros; Medalion, Benjamin; Grizzard, John; Cassano, Anthony; Harris, Timothy
Abstract: Intimal sarcoma (IS) is a rare malignancy arising in the great vessels or heart, most commonly in the pulmonary artery, primarily treated with surgical intervention. We report a case of IS of the pulmonary artery diagnosed after an endarterectomy to remove a suspected pulmonary embolism. The tumor could not be entirely resected and showed interval growth at post-operative follow up. Neoadjuvant radiotherapy was then delivered to improve resectability. Imaging confirmed decreased tumor size, and a surgical resection with pulmonary artery reconstruction and right upper lobectomy was then successfully performed. Adjuvant gemcitabine and docetaxel was later initiated. Four months post-operatively, the patient is alive without disease recurrence. While prior reports in the literature document use of adjuvant chemotherapy and radiotherapy for treatment of IS of the pulmonary artery, no prior experience has documented utility of neoadjuvant radiotherapy for improvement of resectability. Our experience suggests that neoadjuvant radiation should be considered to improve resectability in cases of borderline resectable IS of the pulmonary artery.